(untitled) (Heritage, 2025)
The paper analyzes the political and national activities of Toma Popović, a member of the National Assembly from Gnjilane. Toma Popović came from a well-known old Serbian priestly family, was a merchant, but very early became active in the socio-political sphere. Before the First World War, he was associated with the Movement for the Liberation of Serbs in Kosovo and Metohija. He was engaged in literary work, described folk customs in his area, collected folk tales, and was active in humanitarian societies. During the First World War, he was interned in Bulgaria, but managed to escape, and then cross into Albania with the Serbian army. After the war, he became a member of the Radical Party and was a member of parliament for two terms. When Croatian MP Stjepan Radić was murdered in the National Assembly on June 20, 1928, Toma Popović was also accused, who had been discussing with Radić that day. The murder was preceded by a heated debate in the assembly, in which Radić insulted the deputies by comparing them to "cattle", to which the Serbian deputies reacted vehemently, and Toma Popović stood out in particular. He threatened Radić, "One day dead heads will fall here, but it will not be the Serbs who will be to blame, but them!" This was interpreted as incitement to violence, which preceded the murder, for which Toma Popović was excluded from the work of the assembly. From 1931 to 1941, he withdrew from political life, and engaged in literary work and publishing in Kosovo and Metohija. After World War II, the newly established communist government characterized him as a "royalist" and declared him an "enemy of the people". His property was confiscated, his civil honor was taken away, and only thanks to the involvement of his son did he manage to save his life. He died in 1950 in Gnjilane, completely deprived of his rights in the house of his sister and brother-in-law.